PHONETIC INTERFERENCE COMPETENCE IN ARABIC ARTICULATION FOR CHILDREN WITH DOWN SYNDROME - Hasan, Laili Mas Ulliyah; Aziz, Muhammad Tareh; Nurharini, Firdausi; Machmudah, Umi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
This study endeavors to meticulously assess the efficacy of a straightforward intervention in Arabic for a person with Down Syndrome. The research focuses on a specific subject denoted as MS, representing children with Down Syndrome possessing an extremely low IQ. The subject is perceived as incapable of executing cognitive tasks, including acquiring linguistic capabilities. Through a qualitative approach, this research integrates methods such as observation, interviews, and expert assessments conducted by psychologists to oversee the intervention process. Data collection encompasses the researcher's observational records, interviews, and pertinent documentation. A descriptive analysis methodology is employed for data analysis and presentation. The study reveals discernible enhancements in MS's Arabic pronunciation following the phonetic articulation intervention. Initially, MS could only pronounce the letters Alif, Ta, Jim, Ha, Dal, Za, Sin, Shod, Tho, 'Ain, Fa, Kaf, Lam, Mim, Nun, Ya, Wawu, Hha, Hamzah, but later, MS can also articulate Ba, Tsa, Kho, Dzal, Ro, Syin, Dlod, Dzo, Ghin, Qof, Yak. Throughout the investigation, recurrent challenges manifested as MS encountered difficulties, such as experiencing headaches and multiple crossed eyes in articulating specific phonemes and words during the initial phases of Arabic language acquisition.